Past and present distribution, densities and movements of blue whales Balaenoptera musculus in the Southern Hemisphere and northern Indian Ocean - TA BRANCH; KM STAFFORD; DM PALACIOS; C ALLISON; JL BANNISTER; CLK BURTON; E CABRERA; CA CARLSON; B GALLETTI VERNAZZANI; PC GILL; R HUCKE-GAETE; KCS JENNER; et al. (2007)
Past and present distribution, densities and movements of blue whales Balaenoptera musculus in the Southern Hemisphere and northern Indian Ocean